2020
DOI: 10.3390/su12239795
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Land Use and Transport to Reach Sustainable Development Goals: Will Radical Scenarios Actually Get Us There?

Abstract: The United Nations have developed Sustainable Development Goals (SDG) to guide countries’ development in the next decades. In this paper, we first propose a set of measurable indicators that define the degree of achievement of SDG. Secondly, we use a microscopic integrated land use and transportation model to define future scenarios and measure SDG in the future with radical policies. The model is implemented in Munich and Kagawa. The results are not uniform across policies: while the core cities scenario limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Another study integrated MATSim with an agent-based land-use model [43] to analyze whether SDGs may be achieved by urban and transport policies [44]. Our study will incorporate the land-use model to reflect the population dynamics in Bangkok and will be able to analyze urban and transportation sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…Another study integrated MATSim with an agent-based land-use model [43] to analyze whether SDGs may be achieved by urban and transport policies [44]. Our study will incorporate the land-use model to reflect the population dynamics in Bangkok and will be able to analyze urban and transportation sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…It can be demonstrated that the analyses of such SDG-land-use associations are proven valuable tools to assess the impact of local urban and municipal planning (possibly relocation) policies on urban development. The key aspects of the interrelation between SDGs and the nexus approach in resilient cities and multifunctional land-use systems can stress the importance of economic incentives for successful nexus implementation, providing specific guidance on how to advance sustainable resource management [39][40][41][42][43][44].…”
Section: Land Use and Land Cover Considerationsmentioning
confidence: 99%
“…SDG 11.2 is associated with increasing urban access through affordable, safe, sustainable and accessible transport (Fried et al, 2020). A set of measurable indicators influencing transport and land use policies defines the degree of accomplishment of SDGs (Llorca et al, 2020). Macmillan et al (2020) demonstrated suburb‐level modifications for active transport to achieve the SDGs by presenting a case study of New Zealand.…”
Section: Content Analysismentioning
confidence: 99%